2010
DOI: 10.1177/0300985810389312
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cell Adhesion Molecules and Doublecortin in Canine Anaplastic Meningiomas

Abstract: Tumor cell invasion into the surrounding nervous tissue is one of the histologic hallmarks of anaplastic meningiomas. To identify other possible markers for aggression in canine meningiomas, the relationship between histologic features and the expression of molecules involved in cell adhesion, cell proliferation, and invasion was examined. Immunohistochemistry for epithelial cadherin (E-cadherin), neural cadherin (N-cadherin), b-catenin, doublecortin (DCX), and Ki-67 was performed for 55 cases of canine mening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 23 publications
3
41
2
Order By: Relevance
“…7 Doublecortin is a microtubule-associated protein that is expressed in migrating neurons during development and is highly expressed in invasive brain tumors in humans. 2 Ide et al 3,4 reported the overexpression of doublecortin in canine oligodendroglioma and anaplastic meningiomas. 3 Neoplastic cells in both dogs of this report expressed doublecortin and Olig2, suggesting that the neoplastic cells had a low degree of differentiation and were of oligodendroglial origin.…”
Section: Discussionmentioning
confidence: 99%
“…7 Doublecortin is a microtubule-associated protein that is expressed in migrating neurons during development and is highly expressed in invasive brain tumors in humans. 2 Ide et al 3,4 reported the overexpression of doublecortin in canine oligodendroglioma and anaplastic meningiomas. 3 Neoplastic cells in both dogs of this report expressed doublecortin and Olig2, suggesting that the neoplastic cells had a low degree of differentiation and were of oligodendroglial origin.…”
Section: Discussionmentioning
confidence: 99%
“…9 Additional stem cell markers include nestin, beta III tubulin, and doublecortin, in line with the primitive nature of these tumors. 49 Doublecortin is a regulator of cytoskeletal organization and is involved in neuronal and glial migration; 24 mutations in this gene may result in developmental anomalies such as polymicrogyria. Nestin is an intermediate filament of immature neuronal cells active during development, but it does not separate neuronal and glial tumors in people.…”
Section: Neural Tumorsmentioning
confidence: 99%
“…Doublecortin, not expressed in normal meninges, might with further study become a useful tumor boundary marker. 49 The expression of vascular endothelial growth factor isoforms has been associated with peritumoral edema in a variety of canine brain tumors, but expression in meningiomas is low compared to that observed in high-grade parenchymal tumors. 22 Those meningiomas possessing high levels of vascular endothelial growth factor expression had shorter survival, which may be related to increased tumor vascularity.…”
Section: Meningiomasmentioning
confidence: 99%
“…To improve the knowledge on the biological behavior of meningioma, in the last years the expression of a series of molecules associated with cell adhesion and invasion have been investigated in human and canine meningiomas (Akat et al, 2008;Daou et al, 2005;Ide et al, 2011;Panagopolous et al, 2008;Shimada et al, 2005). Doublecortin (DCX), which plays a crucial role in neuroblast migration during the development of the cerebral cortex, is highly expressed in invasive brain tumors (Daou et al, 2005).…”
Section: Introductionmentioning
confidence: 99%